Ecological aspects of environmental management as the most important national priority - Luneva, Elena V. (Opción, 2019)
The article examines the economy and legal aspects of rational environmental management in the Russian Federation as its most important national priority. The methodological basis of the study was formed by the dialectic method, which enabled us to know, in inseparable unity and in general connectedness, the essence of rational environmental management. As a result, rational environmental management is associated with an increase in the sustainability and productivity of ecological systems. As a conclusion, legal incentives can induce economic actors to incur additional costs to increase the sustainability of ecological systems.